Research on vitrification technology to immobilize radioactive sludge generated from Fukushima Daiichi power plant: enhanced glass medium. Issue 10 (2nd October 2016) - Amamoto, Ippei; Kobayashi, Hidekazu; Kitamura, Naoto; Takebe, Hiromichi; Mitamura, Naoki; Tsuzuki, Tatsuya; Fukayama, Daigen; Nagano, Yuichi; Jantzen, Tatjana; Hack, Klaus
ABSTRACT: The search for an enhanced glass medium to immobilize the sludge at the Fukushima Daiichi Nuclear Power Plant is our main purpose. The iron phosphate glass (IPG) is a potential candidate as we set about assessing it by means of theoretical and experimental investigation. Based on the results of this study, the IPG showed favorable characteristics as a vitrification medium for the sludge.